State of the art review about bio-inspired design and applications: an aerospace perspective - Budholiya, Sejal; Bhat, Aayush; Raj, S. Aravind; Hameed Sultan, Mohamed Thariq; Md Shah, Ain Umaira; Basri, Adi A. (MDPI AG, 2021)
The field of bio-inspired design has tremendously transitioned into newer automated methods, yet there are methods being discovered which can elucidate underlying principles in design, materials, and manufacturing. Bio-inspired design aims to translate knowledge from the natural world to the current trends in industry. The recent growth in additive manufacturing (AM)methods has fueled the tremendous growth of bio-inspired products. It has enabled the production of intricate and complicated features notably used in the aerospace industry. Numerous methodologies were adopted to analyse the process of bio-inspired material selection, manufacturing methods, design, and applications. In the current review, different approaches are implemented to utilize bio-inspired designs that have revolutionized the aerospace industry, focusing on AM methods.